2018
DOI: 10.1088/1674-1056/27/3/034202
|View full text |Cite
|
Sign up to set email alerts
|

Optical encryption of multiple three-dimensional objects based on multiple interferences and single-pixel digital holography

Abstract: We present an optical encryption method of multiple three-dimensional objects based on multiple interferences and single-pixel digital holography. By modifying the Mach-Zehnder interferometer, the interference of the multiple objects beams and the one reference beam is used to simultaneously encrypt multiple objects into a ciphertext. During decryption, each three-dimensional object can be decrypted independently without having to decrypt other objects. Since the singlepixel digital holography based on compres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…In recent years, CS-based optical encryption methods have been increasing the demand for many optical information processing applications [41][42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, CS-based optical encryption methods have been increasing the demand for many optical information processing applications [41][42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…e simulation results have shown that the CS scheme improved the security and reconstruction quality of the intensity image. Wang et al [49] have presented single-pixel compressive holographic encryption by modifying the Mach-Zehnder interferometer setup for multiple-3D-object imaging based on multiple interferences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] Since the DRPE-based optical encryption has high flexibility and expansion capability, consequently, many other optical encryption methods have also been developed, which proves to be feasible and effective. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] In recent years, the vulnerability analysis of optical encryption systems has attracted wide interest from researchers. The DRPE-based optical encryption schemes have been verified to be vulnerable to different kinds of attacks [26][27][28][29] due to its inherent properties of linearity and symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…Holography can simultaneously record the amplitudes and phases of object waves, so this technique is widely used for three-dimensional (3D) display, [1,2] topography measurement, [3,4] information encryption, [5][6][7] and biological cell microscopy. [8][9][10] Initially, the original holography [11] proposed by Gabor has many inherent shortcomings, and the DC and conjugate terms seriously reduce the image quality due to the coaxial optical system.…”
Section: Introductionmentioning
confidence: 99%